Financial Well-Being Resilience : Financial Literacy and Financial Inclusion Toward Financial Attitude - Echan Adam; Roymon Panjaitan; Tantik Sumarlin; Myra Andriana (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Discussion of this research to analyze the resilience of financial well-being derived from financial literacy and the impact of financial inclusion through financial attitudes. A total of 239 respondents were distributed to MSME businesses, especially with data collection techniques in the form of questionnaires and interviews. SEM-PLS compound path analysis was used in this study for data from path analysis mediated by financial attitude on financial well-being resilience. The results of the study there is a positive correlation between the direct relationship of financial literacy and financial inclusion in financial attitudes, as well as positive relationships between financial literacy and financial inclusion through financial attitudes on financial well-being resilience. Then there is the direct positive contribution of financial attitudes to financial security resilience. This study explained that the contribution of financial attitudes can provide positive stimulus in measuring financial well-being resilience from indicators of perception, strength, inadequacy, retention contained in financial attitudes